If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 3x + -9 Reorder the terms: -9 + 6x = 3x + -9 Reorder the terms: -9 + 6x = -9 + 3x Add '9' to each side of the equation. -9 + 9 + 6x = -9 + 9 + 3x Combine like terms: -9 + 9 = 0 0 + 6x = -9 + 9 + 3x 6x = -9 + 9 + 3x Combine like terms: -9 + 9 = 0 6x = 0 + 3x 6x = 3x Solving 6x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = 3x + -3x Combine like terms: 6x + -3x = 3x 3x = 3x + -3x Combine like terms: 3x + -3x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| 2x-4x+10=40 | | 17=9x+5-3x | | -5+-1=22 | | 4?(x?6.3)= | | (7x+5y)(7x+5y)= | | 2r^2-3r+4=r^2+2r+9 | | 10-10x-15y= | | .1r=1 | | X/18-4/6=4/6 | | 5(2m+4)= | | -(a-6)+2=7a+40 | | -13=z-3 | | x+3x-7=0 | | 4g=16 | | -4(-3w-6)=12w+2 | | -18+3(5x-2)+8= | | N^2+24=-10n | | (3/5x)-2=1.3 | | 15+5b=-5(-3b+3) | | 9p-7=7 | | X-(x(.2))=228 | | 6(x-7)-3(4-9)=0 | | (3/5x)-2=1.6 | | 5x-4x-3=3 | | 22=7x+2-3x | | 4(-6x-7)=-28 | | 3(2y-1)=5y+18 | | 2(3h-1)+4h=10(2-3h)+8h | | (3/5x)-2 | | -8n+5n=-15 | | 9x^2+63x= | | 3/4(8x-4)=15 |